NDiVE: Gamified virtual reality environment for logistics and supply chain management training - Teräs, M.; Reiners, Torsten; Coldham, George; Wood, Lincoln (2016)
© 2016 Authors.!Virtual reality (VR) technologies have been under development for decades, but latest more affordable and increasingly available technologies have raised unprecedented interest in using VR for enhancing human capacities, also in higher education learning. This paper will report a summary of a three-year project in developing and studying the use of VR for safety training in Logistics and Supply Chain Management (SCM). The training environment, 'nDiVE', with its technological and learning design developments is presented. Also opportunities and challenges that have emerged during the project, in addition to future research and development opportunities are discussed.